A plan for systematic reviews for high-need areas in forensic science - Jason M. Chin; Anna-Maria Arabia; Merryn McKinnon; Matthew J. Page; Rachel A. Searston (Forensic Science International: Synergy)
Forensic scientific practitioners and researchers must navigate a rapidly growing body of research. This makes it increasingly challenging to inform courts, lawyers, and other decision makers about the state of the field, thus heightening the chances of wrongful convictions and acquittals. When similar challenges have arisen in other fields, they have turned to systematic reviews, which are research reviews that use formal, articulated methods to provide a comprehensive summary of the literature on a specific research question. Systematic reviews allow users to evaluate how the authors identified research and synthesised its findings, making them more transparent than informal literature reviews. This article lays out a justification and plan for systematic reviews in forensic science.